Human Cerebrospinal Fluid Monoclonal LGI1 Autoantibodies Increase Neuronal Excitability - Kornau, Hans‐Christian; Kreye, Jakob; Stumpf, Alexander; Fukata, Yuko; Parthier, Daniel; Sammons, Rosanna P.; Imbrosci, Barbara; Kurpjuweit, Sarah; Kowski, Alexander B.; Fukata, Masaki; Prüss, Harald; Schmitz, Dietmar (Annals of neurology, 2020)
Objective Leucine‐rich glioma‐inactivated 1 (LGI1) encephalitis is the second most common antibody‐mediated encephalopathy, but insight into the intrathecal B‐cell autoimmune response, including clonal relationships, isotype distribution, frequency, and pathogenic effects of single LGI1 antibodies, has remained limited. Methods We cloned, expressed, and tested antibodies from 90 antibody‐secreting cells (ASCs) and B cells from the cerebrospinal fluid (CSF) of several patients with LGI1 encephalitis. Results Eighty‐four percent of the ASCs and 21% of the memory B cells encoded LGI1‐reactive antibodies, whereas reactivities to other brain epitopes were rare. All LGI1 antibodies were of IgG1, IgG2, or IgG4 isotype and had undergone affinity maturation. Seven of the overall 26 LGI1 antibodies efficiently blocked the interaction of LGI1 with its receptor ADAM22 in vitro, and their mean LGI1 signal on mouse brain sections was weak compared to the remaining, non–ADAM22‐competing antibodies. Nevertheless, both types of LGI1 antibodies increased the intrinsic cellular excitability and glutamatergic synaptic transmission of hippocampal CA3 neurons in slice cultures. Interpretation Our data show that the patients’ intrathecal B‐cell autoimmune response is dominated by LGI1 antibodies and that LGI1 antibodies alone are sufficient to promote neuronal excitability, a basis of seizure generation. Fundamental differences in target specificity and antibody hypermutations compared to the CSF autoantibody repertoire in N‐methyl‐D‐aspartate receptor encephalitis underline the clinical concept that autoimmune encephalitides are very distinct entities. Ann Neurol 2020;87:405–418